The Potential of Clitoria ternatea L. Extracts as an Alternative Indicator in Acid-Base Titration - Camalin Bela Sukmaning Fitri*; Retno Aliyatul Fikroh (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
Experiments are an important part of the chemistry curriculum. An indicator in the form of a synthesis indicator is commonly used in acid-base materials experiments. The usage of synthetic indicators can result in waste that is both environmentally harmful and costly. The butterfly pea flower is one of the plants that contains anthocyanins, which have the potential to be used as an alternative indication of natural acids and bases. The study aims to determine the acid and base material curriculum and competency indicators, as well as the potential of butterfly pea flower extract as a substitute for synthesis indicators and the practicality of butterfly pea flower extract as a chemical experimental design in SMA/MA. This study employs a descriptive qualitative research method that includes literature review, observation, experimentation, and interviewing. The results showed that the relationship between acid-base materials and experiments was the determination of natural materials as acid-base indicators, the pH of the solution, the identification of acid-base properties, and acid-base titration. The butterfly pea flower indicator was produced from maceration extraction using 96% ethanol as the solvent. The butterfly pea flower indicator gives pink color at pH 1-2, reddish purple at pH 3, light purple at pH 4-5, turquoise at pH 6, bluish green at pH 7, light blue at pH 8-9, green at pH 10, yellowish green at pH 11, greenish yellow at pH 12-13, and yellow at pH 14. The titration step showed that butterfly pea flower indicators could replace synthetic indicators, namely phenolphthalein and methyl orange. Based on the analysis, the butterfly pea flower indicator can be used as an alternative indicator in acid base titration and an alternative experimental design in schools.